Visual Transmission Deficits in Mice with Targeted Disruption of the Gap Junction Gene Connexin36 - Güldenagel, Martin (J Neurosci, 2001)
In the mammalian retina, rods feed into the cone pathway through electrotonic coupling, and recent histological data suggest the involvement of connexin36 (Cx36) in this pathway. We therefore generated Cx36 null mice and monitored the functional consequences of this deficiency on early visual transmission. The homozygous mutant mice had a normally developed retina and showed no changes in the cellular organization of the rod pathway. In contrast, the functional coupling between AII amacrine cells and bipolar cells was impaired. Recordings of electroretinograms revealed a significant decrease of the scotopic b-wave in mutant animals and an increased cone threshold that is compatible with a distorted, gap junctional transmission between AII amacrine cells and cone bipolar cells. Recordings of visual evoked potentials showed extended latency in mutant mice but unaffected ON and OFF components. Our results demonstrate that Cx36-containing gap junctions are essential for normal synaptic transmission within the rod pathway.